Evaluation of the cross-neutralization activities elicited by Coxsackievirus A10 vaccine strains - Yaqian Huo; Jinghuan Yang; Pei Liu; Bopei Cui; Chenfei Wang; Siyuan Liu; Fangyu Dong; Xujia Yan; Lianlian Bian; Fan Gao; Xing Wu; Jiuyue Zhou; et al. (Taylor & Francis Group, 2021)
Increased severity of diseases caused by Coxsackievirus A10 (CV-A10) as well as a large number of mutants and recombinants circulating in the population are a cause of concern for public health. A vaccine with broad-spectrum and homogenous protective capacity is needed to prevent outbreaks of CV-A10. Here, we evaluated cross-neutralization of prototype strain and 17 CV-A10 strains from related manufacturers in mainland China in vitro using 30 samples of plasma collected from naturally infected human adults and 18 sera samples from murine immunized with the above strains of CV-A10. Both human plasma and murine sera exhibited varying degrees of cross-neutralizing activities. Prototype A/Kowalik and sub-genotype C3/S113 were most difficult to neutralize. Among all strains tested, neutralization of S102 and S108 strains by 18 different sera was the most uniform, suggesting their suitability for detection of NtAb titers of different vaccines for avoiding biases introduced by detection strain. Furthermore, among all immune-sera, cross-neutralization of the 18 strains of CV-A10 by anti-S110 and anti-S102 was the most homogenous. Anti-S102 exhibiting higher geometric mean titer (GMT) in vitro was evaluated for its cross-protection capacity in vivo. Remarkably, administration of anti-S102 protected mice from lethal dosage of eight strains of CV-A10. These results provide a framework for formulating strategies for the R&D of vaccines targeting CV-A10 infections.